The Dissemination of Žemaitė’s Literary Fiction in the Education System in 1905–1914 - Bleizgienė, Ramunė (Literatūra, 2020)
The article describes the syllabi of Lithuanian language subject for public and private schools prepared in 1905-1914 for the developing modern Lithuanian education system with the aim to determine the extent of representation of Žemaitė’s literary fiction. Referring to previous works by V. Pupšys, V. Pukienė, M. Karčiauskienė, A. Piročkinas and analysis of their sources, 9 syllabi of Lithuanian language and their recommended textbooks have been described in this article. The analysis has shown that Žemaitė first established herself in the Lithuanian education system as the author of the textbook Rinkinėlis vaikams, first published in 1904 and intended for primary schools. Žemaitė emerges as the author of short stories and a co-author of dramas for the first time in 1912 in the syllabus published by J. Kairiūkštis. The attention allocated to her and the list of her works is the same as for the majority of other fiction authors of the time. In 1912 M. Biržiška’s project of the Lithuanian language syllabus Žemaitė is referred to as one of the four women prose writers of the end of the 19th century among G. Petkevičaitė-Bitė, Šatrijos Ragana, and Lazdynų Pelėda.